Erratum: Daly, M. & Ljubenkov, J.C. (2008) Edwardsiid sea anemones of California (Cnidaria: Actiniaria: Edwardsiidae), with descriptions of eight new species. Zootaxa, 1860, 1-27. - M., Daly; C., Ljubenkov J. (Zootaxa, 2009)
(Erratum)